Carbon quantum dots for fluorescent detection of nitrite: A review. (30th July 2023) - Guo, Yongming; Wang, Ruiqing; Wei, Chengwei; Li, Yijin; Fang, Tiancheng; Tao, Tao
Highlights: Synthesis of CQDs is briefly discussed. Significant advances in CQDs for fluorescent sensing NO2 − are highlighted. Challenges and perspectives of CQDs fluorescent assay of NO2 − are presented. Abstract: NO2 − is commonly found in foods and the environment, and excessive intake of NO2 − poses serious hazards to human health. Thus, rapid and accurate assay of NO2 − is of considerable significance. Traditional instrumental approaches for detection of NO2 − faced with limitations of expensive instruments and complicated operations. Current gold standards for sensing NO2 − are Griess assay and 2, 3-diaminonaphthalene assay, which suffer from slow detection kinetics and bad water solubility. The newly emerged carbon quantum dots (CQDs) exhibit integrated merits including easy fabrication, low-cost, high quantum yield, excellent photostability, tunable emission behavior, good water solubility and low toxicity, which make CQDs be widely applied to fluorescent assay of NO2 − . In this review, synthetic strategies of CQDs are briefly presented. Advances of CQDs for fluorescent detection of NO2 − are systematically highlighted. Lastly, the challenges and perspectives in the field are discussed.